Proceedings of the 4th International Conference on Economics, Business and Economic Education Science, ICE-BEES 2021, 27-28 Jul 2022
DOI: 10.4108/eai.27-7-2021.2316834
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Instagram on Customer Relationship, Customer Equity, and Purchase Intention Towards Luxury Fashion Brands

Abstract: As the usage of online shopping platforms becomes more important for today's society, luxury fashion brands are prompting to adopt online selling as their distribution channels. Especially in adopting social media marketing on the Instagram platform. However, social media usage brings a dilemma and hesitation to luxury fashion brands because of the different characteristics between social media and the luxury fashion brand itself. Adding that, a lack of studies discusses how luxury fashion brands should use th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Composite Reliability and Cronbach's Alpha interpretations are declared reliable if the values of the two components are ≥ 0.7. According to Utomo (2022), the greater the diversity in the variables contained in the latent construct, the greater the representation of the latent construct [43].…”
Section: Composite Reliability Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite Reliability and Cronbach's Alpha interpretations are declared reliable if the values of the two components are ≥ 0.7. According to Utomo (2022), the greater the diversity in the variables contained in the latent construct, the greater the representation of the latent construct [43].…”
Section: Composite Reliability Testingmentioning
confidence: 99%
“…So it can be concluded that all variables are declared reliable so that they can proceed to the next step. have a positive influence on increasing customer relationship equity in luxury clothing brands [43].…”
Section: Based On Table 2 Cronbach's Alpha Andmentioning
confidence: 99%
“…Social media marketing has proven to affect customer engagement and brand loyalty (Utami & Saputri, 2020). The use of social media has a positive influence on customer relationships and equity, which in turn creates purchase intention (Natiqa, Kusumawati, & Aprilianty, 2022).…”
mentioning
confidence: 99%